2020
DOI: 10.1371/journal.pone.0230531
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific synergistic bio-priming of pepper by two Streptomyces species against Phytophthora capsici

Abstract: Among several studied strains, Streptomyces rochei IT20 and S. vinaceusdrappus SS14 showed a high level of inhibitory effect against Phytophthora capsici, the causal agent of pepper blight. The effect of two mentioned superior antagonists, as single or combination treatments, on suppression of stem and fruit blight diseases and reproductive growth promotion was investigated in pepper. To explore the induced plant defense reactions, ROS generation and transcriptional changes of selected genes in leaf and fruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In the present study, the DEF09 strain showed lower but significant inhibition of fungal growth and toxin production, confirming that mechanisms of fungal growth inhibition are active in this strain also on detached grains. Our study identifies peculiarities of each strain that can be exploited for generating complex consortia able to effectively limit the disease [ 58 , 59 ]. Hopefully, future integration of omics analyses of the biocontrol strains may lead to the identification of effective molecules able to block fungal growth and modulate toxin biosynthesis [ 60 ] as well as to the understanding of mechanisms that modulate growth by sensing the fungal neighbor.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the DEF09 strain showed lower but significant inhibition of fungal growth and toxin production, confirming that mechanisms of fungal growth inhibition are active in this strain also on detached grains. Our study identifies peculiarities of each strain that can be exploited for generating complex consortia able to effectively limit the disease [ 58 , 59 ]. Hopefully, future integration of omics analyses of the biocontrol strains may lead to the identification of effective molecules able to block fungal growth and modulate toxin biosynthesis [ 60 ] as well as to the understanding of mechanisms that modulate growth by sensing the fungal neighbor.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that rhizosphere–microbe interactions are modulated by nutrient availability in the soil that bacterial communities act somewhat independently of plants 41 . In particular, the concentration of available P in the soil adjusted the establishment of them 42 or induced plant immunity through PR1 and WRKY40 gene expression which induced salicylic acid‐dependent responses improving resistance against the pathogen 43 . Recent studies also showed that plants with a superior defense and nutrient acquisition, possibly, have specific microbial communities in the rhizosphere, suggesting a close link between plant growth parameters and rhizosphere microbiota functions.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies reported PR-10 down-regulation, which depended on the time and biotic stress assessed ( Figure 4A ; Table S3 ). PR-10 repression was caused by endophytic and mycorrhizal agents, which form mutualistic symbiotic associations with plants ( Johnson et al., 2003 ; Grunwald et al., 2009 ; Mishra et al., 2018 ; Kiani et al., 2021 ), and when more than one PR-10 was evaluated in different genotypes or plant tissues ( Ding et al., 2015 ; Abbasi et al., 2020 ; Irigoyen et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%